Gain-of-function ANXA11 mutation cause late-onset ALS with aberrant protein aggregation, neuroinflammation and autophagy impairment - Qing Liu; Ye Sun; Baodong He; Haodong Chen; Lijing Wang; Gaojie Wang; Kang Zhang; Ximeng Zhao; Xinzhe Zhang; Dongchao Shen; Xue Zhang; Liying Cui (Acta Neuropathologica Communications)
Abstract Mutations in the ANXA11 gene, encoding an RNA-binding protein, have been implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS), but the underlying in vivo mechanisms remain unclear. This study examines the clinical features of ALS patients harboring the ANXA11 hotspot mutation p.P36R, characterized by late-onset motor neuron disease and occasional multi-system involvement. To elucidate the pathogenesis, we developed a knock-in mouse model carrying the p.P36R mutation. In both heterozygous and homozygous mutant mice, ANXA11 protein levels were comparable to those in wild-type. Both groups exhibited late-onset motor dysfunction at approximately 10 months of age, with similar survival rates to wild-type (> 24 months) and no signs of dementia. Pathological analysis revealed early abnormal aggregates in spinal cord motor neurons, cortical neurons, and muscle cells of homozygous mice. From 2 months of age, we observed mislocalized ANXA11 aggregates, SQSTM1/p62-positive inclusions, and cytoplasmic TDP-43 mislocalization, which intensified with disease progression. Importantly, mutant ANXA11 co-aggregated with TDP-43 and SQSTM1/p62-positive inclusions. Electron microscopy of the gastrocnemius muscle uncovered myofibrillar abnormalities, including sarcomeric disorganization, Z-disc dissolution, and subsarcolemmal electron-dense structures within autophagic vacuoles. Autophagic flux, initially intact at 2 months, was impaired by 9 months, as evidenced by decreased Beclin-1 and LC3BII/I levels and increased SQSTM1/p62 expression, coinciding with mTORC1 hyperactivation. Significant motor neuron loss and neuroinflammation were detected by 9 months, with marked muscle dystrophy apparent by 12 months compared to wild-type controls. These findings implicate the gain-of-function ANXA11 mutation drives late-onset motor neuron disease by early presymptomatic proteinopathy, progressive neuronal degeneration, neuroinflammation, and autophagic dysfunction.